PUBLIC POLICY, DEMOCRACY AND EFFICIENCY: DIFFERENT ACTORS OF THE SAME PLOT - NASCIMENTO NETO, PAULO; Felicidade da Prefeitura Municipal de Curitiba (Editorial Pontificia Universidad Javeriana, 2016)
Debates has been encouraged by the challenges and barriers observed in the implementation of public policies. We start from the presupposition that, in a liberal state, there is a great tension between policies and democracy. Additionally, capitalism is placed into this context in a contradictory way, sometimes in a conflictual relation with the democratic uncertainty, sometimes in a harmonic relation with a democratic state consistent with their interests. In this paper we adopted three analytical categories (efficiency principle, democracy and capitalism), from which we discuss their contradictions and convergences in the implementation of public policies in Brazil.